How Microfluidics Are Used in Modern Science: Lab-on-A-Chip - V. Basil Hans (International Journal of Advance in Molecular Engineering, 2025)
Microfluidics has changed modern research by making lab-on-a-chip (LOC) technologies that combine multiple lab functions into small, portable devices. These little platforms make it easier to correctly handle small amounts of fluid, which saves time, money, reagents, and automation. This article talks about microfluidics and how it helps LOC technology go forward in all areas of science. We look at important uses of biomedical diagnostics, drug development, environmental monitoring, and synthetic biology. This highlights how LOC devices impact the way research is done and how tests are done at the point of care. Improvements in materials, fabrication processes, and digital and AI-based control systems are making LOC platforms more powerful and easier to use. As microfluidic technologies get better, lab-on-a-chip devices will be useful for both academic research and everyday use. LOC devices have changed the way scientists do research in biological diagnostics, environmental sensing, drug research, and chemical synthesis. Microfluidic technologies minimise sample and reagent needs for high-throughput testing and immediate data acquisition. This cuts down on waste and contamination.
Keywords: biomedical applications; lab-on-a-chip (LOC); microfabrication; microfluidics; miniaturised diagnostics; point-of-care testing